Cardiogenic shock - Hochman, Judith S. , 1951-; Ohman, Magnus (Wiley-Blackwell, 2009)
This book is part of the AHA Clinical Series published in conjunction with the American Heart Association in order to focus on high-interest and emerging topics in cardiovascular disease targeted for cardiologists and other interested healthcare providers.